A method to easily control the interfacial interactions between poly(3-hexylthiophene) and graphene oxide in an ultrasonicated solution. Issue 34 (18th August 2020) - Zhang, Xuan; Wei, Nan; He, Jiaxin; Zhou, Jianjun; Huo, Hong
Abstract : Controlling the charge-transfer interaction between poly(3-hexylthiophene) (P3HT) and graphene oxide (GO) is important to improve the performance of P3HT-based devices. Abstract : Controlling the charge-transfer interaction between poly(3-hexylthiophene) (P3HT) and graphene oxide (GO) is important to improve the performance of P3HT-based devices. The structure of P3HT nanofibres can affect the charge-transfer interaction of the P3HT/GO composites. In this work, the amount and molecular order of P3HT nanofibres in P3HT/GO composites (P3HT–GO-BCs) were modulated by the combination of the nucleation effect and the adsorption effect of GO on P3HT in solution after ultrasonication. UV-visible (UV-vis) spectra and Raman spectra verify that variation in the amount and the molecular order of P3HT nanofibres on the GO surface can effectively control the interfacial charge-transfer interaction between GO and P3HT. The properties of P3HT–GO-BCs were compared with the P3HT/GO composites prepared in our previous work (P3HT–GO-ACs). The results indicate that choosing the appropriate time to mix GO with a conjugated polymer is an easy way to modulate the aggregate structure and charge-transfer interaction of P3HT/GO composites.